CULTURAL RESILIENCE IN THE ERA OF GLOBALIZATION: MAINTAINING HERITAGE AND LOCAL WISDOM FOR FUTURE GENERATIONS - Karomah, Lailatul; Masyuri, Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Globalization has brought significant changes in various aspects of life, including culture. Technological developments and the rapid flow of information create intense cultural interactions, but also threaten the preservation of local culture. The cultural identity of a nation faces the challenge of global homogenization, which has the potential to fade traditional heritage and local wisdom. Cultural resilience is defined as a society's ability to maintain local traditions, values and identity amidst foreign cultural pressures. The results of the discussion show that cultural resilience not only protects the world's cultural diversity, but also strengthens the identity of a nation. With an adaptive and inclusive approach, cultural heritage can be passed on to future generations without losing its essential meaning. This article underlines the importance of collaboration between government, society and the younger generation in maintaining cultural resilience amidst globalization